Antimony doped tin oxide/polyethylenimine electron selective contact for reliable and light soaking-free high performance inverted organic solar cells - Georgiou, Efthymios; Papadas, Ioannis T.; Antoniou, Ioanna; Oszajca, Marek F.; Hartmeier, Benjamin; Rossier, Michael; Luechinger, Norman A.; Choulis, Stelios A. (My University, 2019)
We have demonstrated a high-performance low temperature solution processed electron selective contact consisting of 10 at. % antimony doped tin oxide (ATO) and the neutral polymer polyethylenimine (PEI). Inverted organic photovoltaics (OPVs) utilizing ATO/PEI as electron selective contact exhibited high power conversion efficiencies for both the reference P3HT:PCBM and the nonfullerene based P3HT:IDTBR active layer OPV material systems. Importantly, it is shown that the proposed ATO/PEI carrier selective contact provides light soaking-free inverted OPVs. Furthermore, by increasing the thickness of the ATO layer from 40 to 120 nm, the power conversion efficiency of the corresponding inverted OPVs remain unaffected, a parameter which indicates the potential of the proposed ATO/PEI carrier selective contact for high performance light-soaking-free and reliable roll-to-roll printing solutions processed inverted OPVs.
Keywords: Conversion efficiency; Efficiency; Nanocomposites; Organic solar cells; Temperature; Tin oxides